The Effects of Sevoflurane or Remifentanil on the Stress Response to Surgical Stimulus - Alsina, Estíbaliz; Matute, Emilio; Dominguez Ruiz-Huerta, Ana; Gilsanz, Fernando (Current Pharmaceutical Design, 2014)
Tissue injury secondary to surgical lesion produces profound changes in endocrine-metabolic function and defence mechanisms in the patient (inflammatory, immunological), leading to an increase in catabolism, immunosuppression and postoperative morbidity. The best anaesthetic and surgical technique should be capable of modulating this response, especially in major surgery, where it can be most harmful and increase patient morbidity. Many of the changes that maintain homeostasis are controlled by the hypothalamicpituitary- adrenal axis. The autonomic-adrenal response is usually immediate, compared to the hypothalamus-pituitary gland, which is slower and longer lasting. Cytokine synthesis and release are the earliest stages in the response to tissue lesion. The most frequently studied cytokines in surgical stress response are IL-6 and TNF-α. Inflammatory mediator concentrations are direct indicators of perioperative stress, while haemodynamic changes are considered the indirect indicators of this response. Multiple anaesthetic techniques have been described to modify the stress response in patients undergoing elective surgery. The aim of this review is to present clinical evidence on perioperative stress modulation with different anesthetics. We also describe a different point of view in immunomodulation with the intraoperative management of haemodynamic responses with inhalational bolus of sevoflurane or with remifentanil intravenous bolus. The effects of sevoflurane used as an inhalational bolus to counteract patients’ intraoperative haemodynamic responses modulates the immune response the same than opioid remifentanil.
Keywords: cytokines